High Throughput Screening of Small Molecule Libraries for Modifiers of Radiation Responses - Kim, Kwanghee (2011)
PURPOSE: An unbiased approach of drug discovery through high-throughput screening (HTS) of libraries of chemically defined and bioactive small molecule compounds was used to identify modulators of radiation injury with an emphasis on radioprotectors and mitigators rather than radiosensitizers. Assay system endpoints included radiation-induced genotoxicity and DNA damage in yeast and apoptosis in murine lymphocytes. Large-scale data mining of chemically diverse libraries identified agents that were effective with all endpoints. HTS of bioactive compound libraries against murine lymphocytes profiled tetracycline and fluoroquinolone antibiotics and cyclopiazonic acid as having activity, and structure-activity analysis showed a common pharmacophore. Purine nucleosides, the interferon inducer tilorone, and linoleic acid were also identified as potential mitigators of radiation damage that often were also radioprotective. Many of these compounds enhance DNA repair, have anti-inflammatory activity, and stimulate hematopoiesis. Selected compounds within these initial verified hits from both types of libraries identified potent mitigators of lethal whole body irradiation (WBI) in mice. CONCLUSION: In spite of the fact that in vitro HTS has limitations and is unable to fully recapitulate all aspects of the complex in vivo acute radiation response, it identified several classes of molecules that had activity as radioprotectors and radiomitigators of the hematopoietic system in vivo. In the future, addition of 3 dimensional (3D) or stem cell cultures or pathway analysis, may improve the power of HTS, but our findings indicate that common, evolutionary conserved, canonical pathways can be identified that could be exploited to mitigate radiation-induced defects.